The role of the pharmacist in hemotherapy and hemovigilance: Scope review (Research, Society and Development, 2023)
The use of blood and its components are essential to life. Hemovigilance, starting from the transfusion act, guarantees the safety of the donor and recipient. The process for hemotherapy is regulated, which current legislation provides the legal framework for a blood transfusion process with quality and safety. This article aims to map the role of the pharmacist in the transfusion act and present pharmaceutical care strategies. This is a scoping review with a time frame from 2018 to 2023, with publications inserted in any scenarios that develop health action. Of the 15 articles retrieved, only 1 met the inclusion criteria. The study highlights the need for, and importance of the pharmaceutical professional being inserted in the context of hemotherapy, as well as its multidisciplinary integration for decision-making.